An Assessing Study of the Internal Law of the Syrian Basic Education Schools According to the Principles of the Total Quality Management - Ghanem, Thanaa (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The aim of this study is to highlight the extent to which the internal law of basic education schools issued by the ministry of education conforms with the principles of the Total Quality Management (TQM). To achieve this aim, the contents of the internal law were analysed quantitatively and qualitatively. The results show that the internal law has not been designed according to TQM principles deliberately where the vision, the mission, quality councils etc…are not mentioned. However, some articles in the internal law are consistent with TQM principles either directly or indirectly. While some principles are focused on, others are ignored. The principle of focusing on the beneficiary came first (In terms of frequency) despite ignoring work place as beneficiary. The principle of supporting top management came last. A revision of the internal law is suggested as to conform with the TQM principles and also the need for further studies regarding the extent and the actual application of its contents.